Central African Republic: Peacebuilding without peace. Challenges on the road to accountable government - Louisa N. Lombard (Stiftung Wissenschaft und Politik (SWP), 2011)
Fifteen years of UN-led peacebuilding efforts in the Central African Republic (CAR) should have culminated with the elections in January and March of this year. But the elections were far from free and fair, and frustration among the country's rebels and other non-state armed groups has only grown. How did this happen? One reason is that the transitional structures that international agencies advocate - for example political dialogue, disarmament, and elections - have grown out of a vision of how the state ought to be and ignore how politics actually play out on the ground. Because of this, Central African leaders are able to play the peacebuilding game for their own benefit, and peace and democracy slip further away. To foster a more accountable government, would-be peacebuilders must begin by critically assessing where political will for change does and does not lie. Doing so should inspire creative solutions to the security and development challenges confronting the region, such as centring the analysis and resolution of security threats on affected communities themselves rather than placing the central government in the role of lead actor
Keywords: 320